Design and static characteristics measurement of Permanent Magnet Linear Motor (PMLM) for oil palm cutter - Abdul Shukor, Fairul Azhar; Misron, Norhisam; Wakiwaka, Hiroyuki; Tashiro, Kunihisa; Nirei , Masami (2014)
Mechanization of oil palm cutter is one of the ways to improve oil palm fresh fruit bunch (FFB) harvesting productivity. Introduction of CantasTM has become a breakthrough in an effort of developing a mechanized oil palm FFB cutter especially in Malaysia. The CantasTM has proven its capability to improve the harvesting activity through several fields testing result. However, due to operational limitations, a new oil palm FFB cutter named E-Cutter has been proposed. This paper focused on the design and development of E-Cutter’s actuator. A prototype of the E-Cutter’s actuator has been manufactured, and its static characteristics have been measured.